Performance Analysis of CBR Applications on Completely Different Routing Protocols in MANETs (International Journal of Communication Systems and Network Technologies, 2015)
Mobile Ad hoc Networks (MANETs) area unit special reasonably network where node movement is in pre ordered fashion but with high speed as compared to MANETs because of high mobility of nodes then it move in random way, right information in mobile networks can be an advanced. So information sending is not easy due to varied requirements of varied applications in terms of various resources like information and current time. The research work gives performance analysis of four forms of routing protocols on CBR applications. The present paper gives performance of packet delivery ratio, packet loss and packet ratio percent for CBR applications in many situation varied pause times and most, minimum speed of nodes. The scenario of several routing protocols shows variation in many conditions. The performance analysis of varied parameter in terms of Quality of service parameters like packet deliver ratio, packet loss and packet loss percent has been studied by varied altogether totally different conditions of CBR traffic that has provides an insight to packet delivery ratio that in turn area unit typically used to enhance performance of an application in future.
Keywords: MANETs; Routing Protocols; AODV; DSR; DYMO; OLSR; Qualnet; Traffic CBR